An assessment of environmental related key performance indicators of the chemical industries - Alfarsi, Alaa; Jagtap, Sandeep; Salonitis, Konstantinos (IOS Press, 2022)
One of the most critical issues faced by chemical industries is reducing the environmental impact caused due to pollution, which has resulted in global warming and health issues. Most chemical industries monitor and use Key Performance Indicators (KPIs) to control pollution, which is currently done by using various KPI’s that are dependent on the product they are producing. Therefore, a study is conducted using a systematic literature review (SLR) focused on articles published between 2000 and 2022 to identify and categorize various KPIs that manufacturers have used to reduce their respective pollution. The results were divided into four main categories – air, water, land, and other pollution. The results demonstrated that ethylene manufacturing industries are the major contributor to air pollution. The mining, gas, and oil industries significantly resulted in water pollution. The land and groundwater pollution were mainly due to mining industries. The other pollution was mainly due to activities such as maintenance and performance of equipment and quality of raw materials.
Keywords: KPIs; Environmental Impact; Chemical Companies; Chemical industries